Factors associated with hemoglobin levels in children under 6 months of age hospitalized in a pediatric center in Peru: Factores asociados a los niveles de hemoglobina en niños menores de 6 meses de edad hospitalizados en un centro pediátrico de Perú - Mamani-Urrutia, Víctor Alfonso (2023)
Introduction: Anemia is a condition in which there is a low concentration of hemoglobin (Hb) levels. Although many causes of anemia have been identified, there are few studies in which they are related to epidemiological factors in the first months of life.  Objective: To determine the factors associated with hemoglobin levels in children under 6 months of age hospitalized in a specialized pediatric center in Peru. Methods: To determine the factors associated with hemoglobin levels in children under 6 months of age hospitalized in a specialized pediatric center in Peru. Results: 61.4% of the infants were women, and only 6.7% of the proportion of the studied population was less than 1 month old. 6.7% had a low birth weight, and 53.2% had a normal delivery. The level of anemia in hospitalized children under 6 months of age is 66.7%. Conclusions: The factors associated with hemoglobin levels were age, nutritional status, weight for length, and hospital causes. Likewise, an association was found between age and the median Hb in boys and girls aged 0 to 5 months.